2021
DOI: 10.36660/abc.20200378
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da Concentração de Ácido Úrico Sérico no Risco de Doença Cardiovascular: Um Estudo Coorte Realizado no Norte da China

Abstract: Fundamento: Os resultados de estudos anteriores sobre a relação entre ácido úrico sérico (AUS) e o risco de doença cardiovascular (DCV) até agora são inconsistentes devido aos fatores de confusão causados por outros fatores de risco cardiovascular conhecidos. Objetivos: Este estudo tem o objetivo de avaliar a relação entre o AUS e as DCV incidentes em chineses de meiaidade e idosos, que foram estratificados de acordo com o índice de massa corporal (IMC). Métodos: Recrutamos 5.721 participantes com idades entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Various studies indicate a strong association between atherosclerotic disease and serum uric acid [7][8][9][10][11][12]. Feng et al (2018) [13] studied 564 people in China and suggested that serum uric acid levels are associated with the development and progression of atherosclerotic vascular changes. Serum uric acid contributes to the development of ATs, including endothelial damage, oxidative metabolism, and increased platelet aggregation and adhesion [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicate a strong association between atherosclerotic disease and serum uric acid [7][8][9][10][11][12]. Feng et al (2018) [13] studied 564 people in China and suggested that serum uric acid levels are associated with the development and progression of atherosclerotic vascular changes. Serum uric acid contributes to the development of ATs, including endothelial damage, oxidative metabolism, and increased platelet aggregation and adhesion [14,15].…”
Section: Introductionmentioning
confidence: 99%